COMPARATIVE ANALYSIS OF THE RADIATION EXPOSURE ON THE TARGET AND CRITICAL ORGANS WITH 2D AND 3D PLANNING OF RADIATION THERAPY FOR LUNG CANCER - I. A. Gulidov; I. N. Ivanova; D. V. Gogolin; A. I. Gorsky; L. V. Kursova; A. Ju. Bouksha; Yu. A. Ragulin (Сибирский онкологический журнал)
Background and purpose. The purpose of this investigation was to evaluate feasibility, safety and efficacy of radiotherapy for inoperable non-small-cell lung cancer (NSCLC). Various radiotherapy planning methods have been proposed to decrease normal tissue toxicity. We compared 2D-RT with 3D-RT for NSCLC. Parameters assessed included dose to PTV and organ-at-risk (OAR), multiple conformity and homogeneity indices. Material and methods. Initial and re-simulation CT images from 52 consecutive patients with IIB – IIIB NSCLC were used to quantify dosimetric differences between 2D and 3D conformal radiotherapy. Contouring was performed on both CTs, and plans (n=104 plans) and dose-volume histograms were generated. Results. All plans provided comparable PTV coverage. Compared with 2D-RT, 3D-RT significantly reduced the maximum dose to heart (p<0.01), spinal cord (p<0.01), whole lung (p<0.01), esophagus (p<0.02) – Wilcoxon test.